2015
DOI: 10.2217/epi.15.114
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a DNA Methylation Microarray for 850,000 CpG Sites of the Human Genome Enriched in Enhancer Sequences

Abstract: Aim:DNA methylation is the best known epigenetic mark. Cancer and other pathologies show an altered DNA methylome. However, delivering complete DNA methylation maps is compromised by the price and labor-intensive interpretation of single nucleotide methods.Material & methods:Following the success of the HumanMethylation450 BeadChip (Infinium) methylation microarray (450K), we report the technical and biological validation of the newly developed MethylationEPIC BeadChip (Infinium) microarray that covers over 85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
472
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(483 citation statements)
references
References 37 publications
8
472
0
3
Order By: Relevance
“…This study also found that methylation of enhancers correlated with poor prognosis. Improved mapping of enhancer elements and the development of new methylation arrays that include probes for these regions 135 have opened many avenues of investigation still to be explored in this field.…”
Section: Non-promoter Dna Methylationmentioning
confidence: 99%
“…This study also found that methylation of enhancers correlated with poor prognosis. Improved mapping of enhancer elements and the development of new methylation arrays that include probes for these regions 135 have opened many avenues of investigation still to be explored in this field.…”
Section: Non-promoter Dna Methylationmentioning
confidence: 99%
“…Although one of the easiest methods to detect and identify DNA methylation pattern is through the use of Illumina Infinium BeadChip array (the latest technology is the MethylationEPIC BeadChip (Moran et al, 2016)) which is nonetheless very expensive method to be used routinely in forensic analysis, however there are other molecular approaches and techniques which have been known for decades and some of them developed recently for detection and analysis of 5mC methylation pattern (Table 1). It should be noted that all these methods and analyses are based on either bisulfite treatment of DNA or use of methylation-sensitive restriction enzyme(s) or use of an antibody against the methylated base or a combination of them.…”
Section: Methods and Techniques Of Dna Methylation Analysismentioning
confidence: 99%
“…The recently outdated Illumina Infinium Human Methylation 450K BeadChip (Illumina Inc.), had the coverage of > 480,000 CpG sites of the genome, which included 99% of RefSeq genes . This technology has now been superseded by Infinium MethylationE-PIC BeadChip microarray which covers > 850,000 methylation sites, including extra 333,265 CpG sites of enhancer regions made possible by ENCODE and FANTOM5 projects (McCartney et al, 2016;Moran et al, 2016;Pidsley et al, 2016). The methylation data of these CpG sites can be obtained from very low amount of genomic DNA (~250 ng).…”
Section: Illumina Infinium Methylation Assaymentioning
confidence: 99%
“…Microarray slides are scanned and automated software computes a beta (β) value equivalent to methylation percentage. Recently, a new generation of these microarrays which cover 850,000 CG sites in the human genome have been released (Moran et al 2016), although there are questions about the reproducibility of this platform as compared to prior microarrays (Logue et al 2017). The advantages of this method are the relatively simple workflow, comparatively low cost per sample, and automated data analysis.…”
Section: Methylation Microarraysmentioning
confidence: 99%